2021
DOI: 10.1073/pnas.2005753118
|View full text |Cite
|
Sign up to set email alerts
|

Kleine-Levin syndrome is associated with birth difficulties and genetic variants in the TRANK1 gene loci

Abstract: Kleine-Levin syndrome (KLS) is a rare disorder characterized by severe episodic hypersomnia, with cognitive impairment accompanied by apathy or disinhibition. Pathophysiology is unknown, although imaging studies indicate decreased activity in hypothalamic/thalamic areas during episodes. Familial occurrence is increased, and risk is associated with reports of a difficult birth. We conducted a worldwide case−control genome-wide association study in 673 KLS cases collected over 14 y, and ethnically matched 15,341… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 116 publications
1
17
0
Order By: Relevance
“…Gene-wide association studies have shown a link to variants in the TRANK1 gene loci, which is a major gene in bipolar disorder. It has been hypothesized that variants in the TRANK1 region may increase the risk of developing KLS, with a correlation between TRANK1 polymorphisms and difficult births, in patients who have KLS [ 3 ]. A second hypothesis is that there are autoimmune mechanisms that lead to the development of KLS, or at least, contribute to the symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene-wide association studies have shown a link to variants in the TRANK1 gene loci, which is a major gene in bipolar disorder. It has been hypothesized that variants in the TRANK1 region may increase the risk of developing KLS, with a correlation between TRANK1 polymorphisms and difficult births, in patients who have KLS [ 3 ]. A second hypothesis is that there are autoimmune mechanisms that lead to the development of KLS, or at least, contribute to the symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium has shown great promise in patients treated with the medication. It has been found that Lithium may increase the duration of the inter-episodic period over time [ 3 , 14 ]. Anticonvulsants, particularly valproate, have been attempted with the suspicion of thalamic dysfunction and may be used as an alternative to lithium [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pathway analysis also revealed the involvement of circadian regulation genes. This study also showed that variants in the TRANK1 gene region may predispose to KLS in participants with a difficult birth, suggesting that the TRANK1 gene region modulates newborns' response to brain injury, resulting in mental and neurological health consequences [113].…”
Section: Central Disorders Of Hypersomnolencementioning
confidence: 52%
“… 11 In addition, TRANK1 rs71947856 variant was associated with circadian regulation and reported birth difficulties in patients with Kleine‐Levin syndrome, which is a rare disease characterized by severe episodic hypersomnia, with cognitive impairment and apathy or disinhibition. 15 However, the specific function of the TRANK1 gene in BD has not been clarified so far.…”
Section: Trank1 a Risk Gene For Bdmentioning
confidence: 99%
“…An integrated analysis of mRNA co‐expression network revealed that genes highly correlated with TRANK1 were significantly involved in the biological processes related to synaptic plasticity, dendritic spine, axon guidance and circadian rhythm 11 . In addition, TRANK1 rs71947856 variant was associated with circadian regulation and reported birth difficulties in patients with Kleine‐Levin syndrome, which is a rare disease characterized by severe episodic hypersomnia, with cognitive impairment and apathy or disinhibition 15 . However, the specific function of the TRANK1 gene in BD has not been clarified so far.…”
Section: Trank1 a Risk Gene For Bdmentioning
confidence: 99%